The role of mothering in fostering resilience and competence in South African black children - Kaplan, Serenne Gina (My University, 1991)
The idea of psycho-immunity stands as a relatively new field of inquiry focusing on resilience and coping instead of breakdown and pathology. In line with this shift in the literature, the present research has attempted to explore the relationship between the quality of mothering experienced by the child and subsequent patterns of perceived competence revealed by that same child. Black township children were selected as subjects as they are deemed to be a population "at risk" due to the cumulative political and socio-economic exigencies that have affected this community for many years. A total of 72 township children between the ages of 12 -17 were assessed. Both structured and supplementary unstructured instruments were employed in order to measure the quality of the maternal relationship on the one hand, and the child's perception of his/her own competence (or resilience) on the other. Results converged to indicate that for the sample investigated, it was the specific "holding" capacity, availability and involvement of the affectively engaged mother-figure that was most highly correlated with competence of a scholastic nature in early adolescence. Conversely, the intrusive mother who wields power as a parenting style was shown to be more likely to raise a child with a poor sense of social acceptance and competence. These findings provide penetrating insights regarding the potency of the maternal dyad in fostering resilience and competence in off-spring. They offer further understanding of the role of black parenting styles in either promoting or demoting the development of psychologically healthy youths who have the potential to become active participants in a new and more just South Africa.
A Dissertation Submitted to the School of Psychology, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Arts in Clinical Psychology,
Keywords: Resilience (Personality trait) in children -- South Africa.; Performance in children.; Child mental health -- South Africa.; Parent and child -- South Africa.